Phenotypic Distinctions Between Omega-5-Gliadin Allergy and Peanut Allergy: Clinical Profile, Reaction Rates and Triggers, and Quality of Life - Zubrinich CM; Puy RM; O'Hehir RE; Hew M (Journal of Asthma and Allergy, 2022)
Celia M Zubrinich,1,2 Robert M Puy,3 Robyn E O’Hehir,1,3 Mark Hew1,2 1Allergy, Asthma & Clinical Immunology, Alfred Health, Melbourne, Victoria, Australia; 2School of Public Health & Preventive Medicine, Monash University, Melbourne, Victoria, Australia; 3Allergy and Clinical Immunology Laboratory, Department of Immunology and Pathology, Central Clinical School, Monash University, Melbourne, Victoria, AustraliaCorrespondence: Celia M Zubrinich, Email c.zubrinich@alfred.org.auBackground: Different phenotypes of food allergy may exist, exhibiting distinct clinical features, and driven by different pathogenic mechanisms. We compared omega-5-gliadin (O5G) allergy to peanut allergy, focusing on clinical features, reaction rates and triggers, and quality of life (QOL).Methods: We surveyed adults with O5G allergy and peanut allergy regarding their diagnosis, co-morbidities, allergic reactions, and QOL measured by the FAQLQ-AF.Results: We received responses from 43/80 (54%) individuals with O5G allergy and 43/130 (33%) with peanut allergy. Compared to peanut allergic individuals, those with O5G allergy were older at age of onset (37.2 vs 2.5 years, p < 0.001), had fewer additional atopic conditions (0.88 vs 2.93, p < 0.001) or food allergies (0.15 vs 1.86, p < 0.001), and more frequent reactions before diagnosis (1.085 vs 0.29 per month, p < 0.05) Reaction rates improved in both groups following diagnosis. Reactions to peanut were more often triggered by accidental exposure (84% vs 26%, p < 0.001) and being away from home (65% vs 28%, p < 0.001), while reactions to O5G were more often due to deliberate ingestion (30% vs 9%, p < 0.05) or unexpected exercise (35% vs 2%, p < 0.001). Overall QOL score was similar between groups (4.2 in O5G allergy, 4.7 in peanut allergy, p = 0.12), but worse among women and those with additional food allergies.Conclusion: Phenotypic differences between O5G and peanut allergy support the development of different clinical approaches and the possibility of targeting distinct pathogenic mechanisms for prevention and treatment. Quality of life was impaired to a similar degree between groups.Keywords: omega-5-gliadin allergy, wheat allergy, peanut allergy, food allergy, anaphylaxis, wheat-dependent exercise-induced allergy, WDEIA, food-dependent exercise-induced allergy, FDEIA, quality of life, QOL, Australia